Bromate formation in bromide-containing water through the cobalt-mediated activation of peroxymonosulfate. (15th October 2015) - Li, Zhaobing; Chen, Zhi; Xiang, Yingying; Ling, Li; Fang, Jingyun; Shang, Chii; Dionysiou, Dionysios D.
Abstract: Bromate formation in bromide-containing water through the cobalt (Co)-mediated activation of peroxymonosulfate (PMS) was investigated. Increasing the PMS dosage and the cobalt dosage increased the formation of bromate and bromate yields of up to 100% were recorded under the test conditions. The bromate yield increased to a maximum as the pH rose from 2.7 to 6 before decreasing by over 90% as the pH rose further from 6 to above 9. The bromate formation is a two-step process involving free bromine as a key intermediate and bromate as the final product. In the first step, apart from the known oxidation of bromide to free bromine and of free bromine to bromate by sulfate radicals (SO4 − ), Co(III) produced from the oxidation of Co(II) by PMS and SO4 − also oxidizes bromide to free bromine. The contribution of Co(III) to the bromate formation was verified with the addition of methanol and EDTA, a radical scavenger and a Co(III) ligand, respectively. In the presence of methanol, free bromine formation increased with increasing Co(II) dosage but no bromate was detected, indicating that Co(III) oxidized bromide to form free bromine but not bromate. In the presence of both EDTA and methanol, no free bromine or bromate was detected, as Co(III) was stabilized by EDTA to form the Co III EDTA – complex, which could not oxidize bromide. Mathematical simulation further suggested that Co(III) outweighed SO4 − to oxidize bromide to free bromine. On the other hand, SO4 − is essential for the oxidation of free bromine to bromate in the second step. In real water, the presence of NOM significantly decreased the bromate formation but caused the brominated organic DBP formation with high quantity. This is the first study to demonstrate the significant bromate formation in the Co/PMS system and the substantial contribution of Co(III) to the formation. Graphical abstract: Highlights: Bromate formation from the Co/PMS process was investigated. The bromate formation is a two-step process involving free bromine as a key intermediate. Co(III) outweighs SO4 − to oxidize bromide to free bromine. SO4 − is essential for the oxidation of free bromine to bromate. NOM decreased the bromate formation but caused the brominated DBP formation.